P25 Retrospective analysis of patients presenting with acute pulmonary embolism (pe) as the first manifestation of malignancy. (15th November 2016) - Murchison, A; Asher, A; Manen, A Van; Ellis, H
Abstract : Introduction: A link between development of PE and presence of malignancy has long been established. NICE recommends patients presenting with PE should be offered: history, examination, chest x-ray and urinalysis. Further investigation for cancer with abdomino-pelvic CT (CT A/P) scan in patients over 40 with a first unprovoked PE should be considered. 1 CT screening has not been shown to improve occult cancer diagnosis or mortality from cancer. 2 Methods: We conducted a retrospective review of patients diagnosed with new PE at Milton Keynes hospital between August 2014 and 2015 to determine the proportion of patients found to have malignancy after CT. Selected patient notes were interrogated for clinical and laboratory findings at the time of diagnosis, and for details of subsequent management. Results: 177 patients were included in our study. 102 received a CT A/P, 88 of whom did not have an established diagnosis of cancer. Out of the 88, 5 new diagnoses of cancer were made. In 10 cases, CT revealed incidental findings. 8 patients received further imaging, and 2 investigated with invasive procedures. 4 of the 5 new cancer diagnoses had abnormal findings after basic screening. Standardised incidence ratios were calculated to assess the probability of presence of undiagnosed cancer in patients presenting with PE. Our data showed no significant increase in the incidence of cancer in patients presenting with PE compared to national cancer statistics (SIR of 0.75 in males (CI: 0.2–0.64) and 1.0 in females (CI: 0.23–0.56) aged 70–79). Discussion: Our data suggests that in patients presenting with acute PE, clinical acumen (as outlined by NICE) can be used to identify patients with potential malignancy. Our data would support limiting CT A/P to patients with significant clinical features or deranged tests. References: National Institute for Health and Clinical Excellence. Venous thromboembolic diseases: diagnosis, management and thrombophilia testing. CG144. NICE 2015. Carrier M, Lazo-Langner A, Shivakumar S, et al . Screening for occult cancer in unprovoked venous thromboembolism. New England Journal of Medicine 2015;373 (8):697–704.